Young women's body image following upwards comparison to Instagram models: The role of physical appearance perfectionism and cognitive emotion regulation. (September 2021) - McComb, Sarah E.; Mills, Jennifer S.
Highlights: Comparison to idealized bodies on Instagram resulted in lowered confidence. Comparison to idealized bodies on Instagram resulted in increased body dissatisfaction. Physical appearance perfectionism predicted negative body image after body comparison. Rumination mediated the relationship between appearance perfectionism and body image. Catastrophizing mediated the relationship between appearance perfectionism and body image. Abstract: The present study examined whether trait physical appearance perfectionism moderates young women's body image following upwards appearance comparison to idealized body images on social media, and whether cognitive coping mediates the relationship between physical appearance perfectionism and resulting body image from social comparison processes. Female undergraduate students ( N = 142) were randomly assigned to either 1) compare the size of their body parts to the body parts of attractive Instagram models, or 2) an appearance-neutral control condition. All participants completed measures of trait physical appearance perfectionism, pre and post measures of state body image, and state cognitive coping processes. Appearance comparison to the models resulted in lowered confidence and increased appearance and weight dissatisfaction. High trait physical appearance perfectionism predicted lower confidence and higher weight dissatisfaction and appearance dissatisfaction, and these relationships were mediated by engagement in rumination and catastrophizing. Clinical implications of the findings are discussed.